RETRACTED: Anusha et al. Dynamics of MHD Convection of Walters B Viscoelastic Fluid through an Accelerating Permeable Surface Using the Soret–Dufour Mechanism. Appl. Sci. 2022, 12, 9431 - P. Anusha; M. Naga Swapna Sri; Vallabhaneni Venkata Venu Madhav; Ch. Sri Chaitanya; V.V. Spandana; Kuldeep K. Saxena; Dalael Saad Abdul-Zahra; Emanoil Linul; Chander Prakash; Dharam Buddhi; Raul Campilho (Applied Sciences)
The Journal retracts the article, “Dynamics of MHD Convection of Walters B Viscoelastic Fluid through an Accelerating Permeable Surface Using the Soret–Dufour Mechanism” [...]